Tree Growing at Farm in Eastern and Western UP, India: a Comparative Analysis of Adoption Issues - Kumar, Nandan; Pandey, Rajiv; Ashraf, Jawaid (Indian Forester, 2011)
Planting trees outside forests will be an additional source of raising forest cover. However, there is large disparity within the farmer communities for tree planting at their farm at regional scale. This study has considered addressing the issue of adaptation of tree planting in two regions of UP for comparison. These are the Western region with high density of tree plantation at farm; and Eastern region with low density. The information related to social, economic and decision making environment within households besides the infrastructural, extension and technical aspects were collected through pretested questionnaire from 39 and 66 randomly selected households from Eastern and Western UP respectively. Economic motives in tree growing are evident in the share of commercial forest tree species in the farm forest tree content. The study concludes that social and economic environment within the households governs the tree planting on both the regions besides external factors. The farmers of Western UP have better access for market (79%), industry accessibility (83%), cheap transport and agents (89% and 76%), planting materials availability (75%) and loan facility (65%) in comparison to Eastern UP, where these practices are quite low. Association analysis confirms that the land and economic status were influencing the adaptation decisions. Based on the stepwise regression analysis for households’ contextual factors, a regular flow of off-farm incomes adds to investible capacity of farm households and encourages tree growing. That the heterogeneity in adoption decision is a function of myriad of factors, which includes intrinsic characteristics of household and state affairs, for the training and extension besides the functionality of the regulatory bodies. Therefore, policy and programme should address both the economic motives of farmers and other associated factors for encouraging tree planting.